2018
DOI: 10.5539/ijbm.v13n9p222
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Cash Holding of Non-Financial Firms Listed on the Nairobi Securities Exchange

Abstract: A general rise in the cash holding levels by firms internationally in the recent years has led to an increase in interest in cash holding research as cash is an asset that typically yields low return. Empirical research has produced mixed results and often little research has been carried out on the subject in developing countries. This paper thus looks at the determinants of cash holding of 44 non-financial firms listed in Nairobi securities exchange (NSE) for the period 2002 to 2013 using secondary data in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
2
3
2
1
Order By: Relevance
“…This result is in line with the research of (Astuti et al, 2019), who found cash flow did not affect the determination of the amount of cash holding. The results of this study are not in line with research from (Barasa et al, 2018;Jebran et al, 2019;Maheshwari and Rao, 2017;Sari and Ardian, 2019;Tayem, 2017) where they found that there was a significant positive relationship between the level of the company's cash flow and the determination of the amount of cash holding. The results of this study are also not in line with those (Liadi and Suryanawa, 2018), who found a significant effect in a negative direction between the level of cash flow and the amount of cash holding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is in line with the research of (Astuti et al, 2019), who found cash flow did not affect the determination of the amount of cash holding. The results of this study are not in line with research from (Barasa et al, 2018;Jebran et al, 2019;Maheshwari and Rao, 2017;Sari and Ardian, 2019;Tayem, 2017) where they found that there was a significant positive relationship between the level of the company's cash flow and the determination of the amount of cash holding. The results of this study are also not in line with those (Liadi and Suryanawa, 2018), who found a significant effect in a negative direction between the level of cash flow and the amount of cash holding.…”
Section: Discussioncontrasting
confidence: 99%
“…A positive relationship between the level of a company's cash flow and determining the amount of cash holding was found by (Barasa et al, 2018;Jebran et al, 2019;Maheshwari and Rao, 2017;D. M. Sari and Ardian, 2019;Tayem, 2017).…”
Section: Theoretical Reviewmentioning
confidence: 98%
“…MB, another control for growth opportunities, was also found to be insignificant. The result is consistent with Barasa et al (2018). However, it is not in line with the predictions of the accelerator theory, Tobin's Q theory and the majority of previous studies, which have reported a positive relation (Kim et al, 1998;Opler et al, 1999;Ferreira and Vilela, 2004;Ozkan and Ozkan, 2004;Alkhataybeh, 2018).…”
Section: Resultscontrasting
confidence: 54%
“…Berdasarkan hasil penelitian diketahui bahwa Ukuran Perusahaan tidak berpengaruh terhadap cash holding perusahaan. Hasil penelitian ini sejalan dengan hasil penelitian terdahulu [14] [15]. Ukuran perusahaan merupakan skala yang dapat mengukur besar kecilnya perusahaan, perusahaan yang dikategorikan besar berdasarkan ukuran total aset yang dimiliki menggambarkan adanya total aset yang besar dan memadai dalam menghasilkan jumlah produksi yang besar.…”
Section: B Peran Cash Holding Dalam Memediasi Ukuran Perusahaan Terha...unclassified